Specialization of the brain for language in children with Fragile X Syndrome: a functional Near Infrared Spectroscopy study - Elizabeth Smith; Kelli C. Dominick; Lauren M. Schmitt; Ernest V. Pedapati; Craig A. Erickson (Journal of Neurodevelopmental Disorders)
Abstract Specialization of the brain for language is early emerging and essential for language learning in young children. Fragile X Syndrome (FXS) is a neurogenetic disorder marked by high rates of delays in both expressive and receptive language, but neural activation patterns during speech and language processing are unknown. We report results of a functional Near Infrared Spectroscopy (fNIRS) study of responses to speech and nonspeech sounds in the auditory cortex in a sample of 2- to 10-year-old children with FXS and typically developing controls (FXS n = 23, TDC n = 15, mean age = 6.44 and 7.07 years, respectively). Specifically, we measured changes in oxygenated and deoxygenated hemoglobin in the auditory cortex during blocks of speech and nonspeech matched noise in children with FXS and sex-and-age-matched controls. Similar to controls, children with FXS showed hemodynamic change consistent with neural activation of the primary auditory regions for speech as well as leftward lateralization for speech sound processing, strength of which was associated with higher verbal abilities in FXS. However, while controls showed neural differentiation of speech and nonspeech in the left auditory cortex, children with FXS did not demonstrate differentiation of the two conditions in this study. In addition, the children with FXS showed a greater neural activation to the nonspeech condition overall. Overall, these results suggest that basic patterns of neural activation for speech are present in FXS in childhood, but neural response to nonspeech sounds may differ in FXS when compared to controls.